Fenomena Isu-Isu Gender Dalam Konseling Multibudaya Di -Indonesia : Fenomena Kawin Tangkap (Piti Rambang) - Bakhrudin All Habsy; Laura Maulita Agustin; Annur Rizqiah Putri Wijaya (Lembag, 2025)
This research discusses the phenomenon of gender issues in multicultural counseling in Indonesia, focusing on the tradition of Kawin Tangkap (Piti Rambang) in Sumba tribe, East Nusa Tenggara. The purpose of the research is to analyze the social and psychological impact of the practice of Kawin Tangkap on women, as well as how multicultural counseling can provide solutions. The research method used was a literature study, which involved collecting and analyzing data from various sources, including journals, articles, and documents related to gender issues. The results showed that the Kawin Tangkap tradition is a form of gender-based violence that violates women's rights and contradicts positive law.